2020
DOI: 10.32604/phyton.2020.09125
|View full text |Cite
|
Sign up to set email alerts
|

Biochar-Induced Priming Effects in Young and Old Poplar Plantation Soils

Abstract: The priming effect (PE) induced by biochar provides a basis for evaluating its carbon (C) sequestration potential in soils. A 60 days' laboratory incubation was conducted, which involved the amendment of biochar (1% of soil mass) produced from rice straw at 300ºC (B300) and 500ºC (B500) to young (Y) and old (O) poplar plantation soils, with the aim of studying the responses of biochar-induced PEs to poplar plantation ages. This incubation included six treatments: Y + CK (control), Y + B300, Y + B500, O + CK, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…These results indicate that biochars and aged biochars have a negative priming effect (PE) on CO 2 -C evolution. Biochars produced at high temperatures are commonly reported to induce negative PEs (Zimmerman et al, 2011;Lu et al, 2020). Negative PEs induced by biochars pyrolyzed at high temperatures are thought to result from a reduction in the availability of native SOC, due to (1) the increase in adsorption capacity of biochar (Kimetu and Lehmann, 2010;Cross and Sohi, 2011), because of the increase of specific surface area of biochar and the decrease of mineralizable C (Kasozi et al, 2010;Conte and Laudicina, 2017), and (2) the formation of stable aggregates that physically protect SOC (Kader et al, 2010;Lu et al, 2014).…”
Section: Comparisons Of C Mineralization Among Treatmentsmentioning
confidence: 99%
“…These results indicate that biochars and aged biochars have a negative priming effect (PE) on CO 2 -C evolution. Biochars produced at high temperatures are commonly reported to induce negative PEs (Zimmerman et al, 2011;Lu et al, 2020). Negative PEs induced by biochars pyrolyzed at high temperatures are thought to result from a reduction in the availability of native SOC, due to (1) the increase in adsorption capacity of biochar (Kimetu and Lehmann, 2010;Cross and Sohi, 2011), because of the increase of specific surface area of biochar and the decrease of mineralizable C (Kasozi et al, 2010;Conte and Laudicina, 2017), and (2) the formation of stable aggregates that physically protect SOC (Kader et al, 2010;Lu et al, 2014).…”
Section: Comparisons Of C Mineralization Among Treatmentsmentioning
confidence: 99%
“…Biochar, a solid material obtained from the thermochemical conversion of biomass in an oxygen-limited environment, has attained extensive attention due to its agronomical and environmental benefits in agroecosystems [8][9][10][11]. Regarding to the effects of biochar on N cycling in vegetable production system, many literatures reported its influences on NH 3 volatilization and N 2 O emission from both stable crop and vegetable production systems [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Glycosylation as a diverse protein post-translational modification (PTM) plays crucial roles in various biological processes of living organisms. 1,2 It is well demonstrated that functions of proteins are frequently modulated by different types of glycans added to either asparagine (N-linked) or serine/threonine (O-linked) residues. [3][4][5] Aberrant glycosylation is also involved in numerous diseases.…”
Section: Introductionmentioning
confidence: 99%